Goodfellas - Scorsese, Martin; Winkler, Irwin; De Niro, Robert; Liotta, Ray; Pesci, Joe; Bracco, Lorraine 1955-; Sorvino, Paul; Pileggi, Nicholas (Warner Home Video, 1990)
Martin Scorsesess GOODFELLAS is a wry, violent, and exhilarating film about the life of Henry Hill, an aspiring criminal who ends up in the FBI's witness protection program after testifying against his former partners. As a poor Irish-Italian growing up in 1950s New York City., Hill rises through the ranks of his Brooklyn neighborhood's organized crime branch, and with money from the mob he begins living the good life, complete with a beautiful wife...